Sports Marketing Dalam Menarik Minat Penonton Formula E di Indonesia - Reinaldo Alfario; Chandra Kuswoyo (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
This research was conducted to test and find out the influence of sports marketing (sports advertising, star athletes, and sports sponsorship) in attracting Formula E spectators in Indonesia. Quantitative approach is the technique used in this study. Data collection was carried out by distributing online questionnaires and a total of 135 respondents were obtained. Data was collected using an online survey. After being created using the Google Form, the questionnaire was distributed to the Indonesian people online. Questionnaire measurements were carried out using a Likert scale, where 1 indicated strongly disagree and 5 indicated strongly agreed. Testing is done by testing the instrument, namely testing the validity and reliability of the questionnaire. The analysis technique used is multiple regression analysis. The research findings found that there is a simultaneous effect of sports advertising, star athlete, and sports sponsorship variables on audience interest. Meanwhile, based on partial research results, the elements of sports marketing that influence audience interest are sports advertising and star athletes. Sports sponsorship does not have a significant influence in attracting audience interest.